Terminal sliding mode control on autonomous underwater vehicle in diving motion control - Nira Mawangi Sarif; Rafidah Ngadengon; Herdawatie Abdul Kadir; Mohd Hafiz A. Jalil (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
In this study, mechanism for reducing chattering in discrete conventional sliding mode controller (DSMC) for autonomous underwater vehicle (AUV) was designed in discrete time domain. The combination of reaching law approach and discrete terminal sliding mode control (DTSMC) scheme was employed to alleviate chattering effect caused by quasi sliding mode (QSM). First, 6 DOF NPS AUV II equation of motion is linearized to diving mode subsystem. Second, linear sliding surface in discrete time domain is designed and reaching law based (RLB) is employed to the control law. Thirdly, discrete nonlinear sliding surface, specifically DTSMC is designed to reduce chattering phenomena and improved precision control simultaneously. Finally, comparative experimental results are presented to illustrate the effectiveness and advantages of the nonlinear sliding surface.